From Local Wisdom to The Global Agenda - Sholihah, Dawimatus; Faizal, Ahmad; Ramadhani, Kurniawan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This research investigates the 'Matoron Roma' tradition as a manifestation of local wisdom in Bondowoso Regency, Indonesia, specifically examining its intersection with Islamic economic principles, social harmony, and the Sustainable Development Goals (SDGs). Utilizing a descriptive qualitative approach supported by interviews and participant observation, the study explores how communal practices foster social cohesion and economic resilience. The findings demonstrate that Matoron Roma actively implements Islamic economic values, including ta'awun (mutual assistance), shodaqoh (voluntary giving), and musyarakah (partnership), through the traditional framework of mutual cooperation (gotong royong). The study concludes that this tradition serves as a localized driver for multiple SDGs: reducing poverty by easing economic burdens related to housing (SDG 1); promoting social justice through non-discriminatory participation (SDG 10); building resilient human settlements (SDG 11); and fostering peace and inclusive institutions through strengthened communal brotherhood (SDG 16). Ultimately, Matoron Roma exemplifies how indigenous traditions can be transformed into sustainable development solutions, representing a vital partnership (SDG 17) that bridges religious ethics with global developmental objectives.